eCM 2021
DOI: 10.22203/ecm.v041a02
|View full text |Cite
|
Sign up to set email alerts
|

Sintered S53P4 bioactive glass scaffolds have anti-inflammatory properties and stimulate osteogenesis in vitro

Abstract: Bioactive glasses (BAG) are used as bone-graft substitutes in orthopaedic surgery. A specific BAG scaffold was developed by sintering BAG-S53P4 granules. It is hypothesised that this scaffold can be used as a bone substitute to fill bone defects and induce a bioactive membrane (IM) around the defect site. Beyond providing the scaffold increased mechanical strength, that the initial inflammatory reaction and subsequent IM formation can be enhanced by coating the scaffolds with poly(DL-lactide-co-glycolide) (PLG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Interestingly µCT scans showed positive effects of S53P4 on the surrounding bone tissue with increased bone volume, indicating an osteoinductive effect of the bone graft substitute, at least under non-infected conditions as seen by other groups [47,48]. This early osteoinductive effect of S53P4 could even be detected in infected conditions 4 weeks after the second surgery.…”
Section: Discussionmentioning
confidence: 66%
“…Interestingly µCT scans showed positive effects of S53P4 on the surrounding bone tissue with increased bone volume, indicating an osteoinductive effect of the bone graft substitute, at least under non-infected conditions as seen by other groups [47,48]. This early osteoinductive effect of S53P4 could even be detected in infected conditions 4 weeks after the second surgery.…”
Section: Discussionmentioning
confidence: 66%
“…We believe that this high expression of osteogenic protein markers may be attributed to the ions released from BG, including Ca, P, and Si, and the release of Laponite mineral constituents including Si, Li, and Mg, which all have a positive role in the osteogenic differentiation according to the recent literature. 45 , 49 , 51 , 108 , 109 Additionally, we evaluated the osteogenic capacity of all combinations by looking at ALP expression and activity. It was found that BGH showed significantly more ALP positively stained areas and resulted in higher ALP activity compared to the other groups in both (±) differentiation media after 1 and 2 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…BAG-S53P4 is a safe and well-tolerated bone-graft material and has successfully been used in the treatment of bone cysts and cavities, including treatment of those arising from infection. Bone formation in experimental in vitro and in vivo bone defect models of BAG-S53P4 has been well documented (24,25).…”
Section: Discussionmentioning
confidence: 99%